Graphic Presentation - Brinton, Willard Cope (Brinton Associates, 1939)
Graphic Presentation is largely a collection of interesting charts and pictures, mostly of a non-technical nature,covering a wide range of subject matter, with brief comment on methodology under each illustration. These charts and pictures are reproductions from numerous sources, including a few from his Graphic Methods. In addition to the chapters on types of charts and excerpts from Time Series Charts: A Manual of Design and Construction published by the American Society of Mechanical Engineers, there are some quasi-technical chapters on such things as the use of cameras and lantern slides, selection of paper, and methods of reproduction, printing, and binding. A chapter on tabulation is thrown in, apparently for good measure. Illustrations on alternate pairs of facing pages arc in color, and these pages contain also decorative chapter identification (bleed-outs) at the top and bottom. Printing was done by the photo offset process. The verbal language is Basic English. A minor feature of the book is a device whereby the reader may spin the pages rapidly until he reaches the desired chapter. On page 453 is given a detailed description of how the book was made up, including the names and addresses of the companies furnishing materials or services. This book departs from the earlier contribution in several respects. Text material is boiled down almost to the vanishing point, leaving the maximum number of charts to speak for themselves.